MarA, RamA, and SoxS as Mediators of the Stress Response: Survival at a Cost - Holden, Emma R.; Webber, Mark A. (Frontiers in Microbiology, 2020)
To survive and adapt to changes in environments, bacteria have evolved mechanisms to express appropriate genes at appropriate times. Exposure to antimicrobials triggers a global stress response in Enterobacteriaceae, underpinned by activation of a family of transcriptional regulators, including MarA, RamA and SoxS. These control a programme of altered gene expression allowing a rapid and measured response to improve fitness in the presence of toxic drugs. Increased expression of marA, ramA and soxS upregulates efflux activity to allow detoxification of the cell. However, this also results in trade-offs in other phenotypes, such as impaired growth rates, biofilm formation and virulence. Here, we review the current knowledge regarding the trade-offs that exist between drug survival and other phenotypes that result from induction of marA, ramA and soxS. Additionally, we present some new findings linking expression of these regulators and biofilm formation in Enterobacteriaceae, thereby demonstrating the interconnected nature of regulatory networks within the cell and explaining how trade-offs can exist between important phenotypes. This has important implications for our understanding of how bacterial virulence and biofilms can be influenced by exposure to antimicrobials.